INFILTRATION KINETICS STUDY AND PROCESSING OF LAYERED GRADED Al2O3-ZrO2 COMPOSITE - Dwi Asmi (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2006)
INFILTRATION KINETICS STUDY AND PROCESSING OF LAYERED GRADED Al2O3-ZrO2 COMPOSITE. Layered graded Al2O3-ZrO2 composite was successfully synthesised through infiltration of porous Al2O3 preform with a solution containing ZrOCl2.8H2O. The infiltration rate of liquid into porous Al2O3 preformhad also been investigated. It was found that the infiltration rate equation proposed by Washburn is most suitable for describing the effects of preform sintering temperature, viscosity and multiple infiltrations on the infiltration behaviour, whereas the influence of applied pressure is consistent with the model proposed by Darcy, where the applied pressure enhances the infiltration rate behaviour. Depth profilling of layered graded Al2O3-ZrO2 composite was characterised by x-ray diffraction, the result shows that the concentration of ZrO2 decreased with depth, while that of Al2O3 increased with depth.